All alone we go faster, together we go further: The necessary evolution of professional and elite sporting environment to bridge the gap between research and practice - Brocherie, F.; Beard, A. (Frontiers in Sports and Active Living, 2021)
The landscape of the professional and elite sport has changed enormously in recent years, with clubs/franchises and national federations performance support operating through specialized background staff roles. Although not uniformly embraced across all sports and countries, the expansion of such a model has led to the emergence of a managing position—generally termed performance director (Buchheit and Carolan, 2019)—to organize and supervise all the sports science and sports medicine servicing areas accessible to the head coach (and/or his technical staff) and athletes. The scientific support staffing base includes full-time sport scientists, physiologists, biomechanists, nutritionists, psychologists, and even more recently statisticians/data scientists, with some additional part-time input from expert/academic consultants (e.g., neuroscientists). Depending of the size and culture of the clubs/federations, a medical department covers the medical care and therapy related to training and competition, as well as the involvement of professional specialists for health management (Dijkstra et al., 2014). As an example, a National Football League (NFL) staff generally comprised five departments and as large as 13 full-time employees under the umbrella of the performance director (Figure 1A). All these departments operate in synergy and also "independently" with appropriate autonomy at times, with the performance director orchestrating the "front lines" in a holistic and comprehensive manner toward a common performance goal.